Biomechanical, operative and biological aspects of the cervical margin relocation: a case report - Prado, Taiana Paola; Chun, Eliseo Pablo; Augusto, Marina Gullo; Bernardon, Paula; Grassi, Elisa Donaria Aboucauch; Saavedra, Guilherme de Siqueira Ferreira Anzaloni; Mathias-Santamaria, Ingrid Fernandes; Santamaria, Mauro Pedrine; Schmitt de Andrade, Guilherme (Brazilian Dental Science, 2022)
The clinical success of tooth-colored indirect restorations has been confirmed in several studies. However, inlays andonlays restorations in Class II cavities with deep gingival margins can still be considered a clinical challenge. Withthe purpose of facilitating the execution of the operative procedures in intrasulcular margins and reducing the riskof restorative failures, the technique of cervical margin relocation has been explored as a noninvasive alternative tosurgical crown lengthening. This work aims at discussing through a case report the biomechanical, operative andbiological aspects in the treatment of teeth with deep gingival margins. Therefore, given the therapy applied in theclinical case presented, it is concluded that the cervical margin relocation with composite resin is advantageous sinceit eliminates the need for surgery, allowing the implementation of indirect restorations in fewer clinical sessions,not causing damage to periodontal tissues once it provided good finishing and polishing with the establishment ofa correct emergence profile, allowing flawless maintenance of gingival health after one year.KEYWORDSDental restoration failure; Dental marginal adaptation; Dental Cavity Preparation; Composite Resins; Inlays.